If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3b + -7 = 20 Reorder the terms: -7 + -3b = 20 Solving -7 + -3b = 20 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -3b = 20 + 7 Combine like terms: -7 + 7 = 0 0 + -3b = 20 + 7 -3b = 20 + 7 Combine like terms: 20 + 7 = 27 -3b = 27 Divide each side by '-3'. b = -9 Simplifying b = -9
| 7y-5-2y=-20 | | 20=4v+16 | | 5x-16=4x-6 | | 3(x+5)-10x+7=50 | | 5v+v-120=0 | | (4x-16)/(3-x)*(x-3)/4 | | a/a | | -4r^2=-152 | | 80-4(3x+10)=-12x+120 | | 5x^2+3=68 | | 3g-2=5g | | 3(p-1)=3p-2 | | -x+7=2x+13 | | -7w-35=2(w+5) | | X/6=54 | | -x+5=2x-11 | | 5x-12=-2y+3 | | -3/4x-7/8 | | 8(v+7)=-5v-48 | | 3(13-2a)=-13+a | | x-5=-2x+13 | | X+80+2x+20=180 | | X/4-x/12=1/2 | | 10r+15=33-12r-52 | | 5-2x/-3-4-x | | [u-7]=-1/4 | | y-9=4/6(x-3) | | -9y-18=9(y-6) | | 2(a+4)=-3(7x+2)+8x | | -2(x-4)=(3-x) | | 3[-2(x+5)-5]=x+7 | | (y^4)-12*(y^3)+48*(y^2)-145*y+90=0 |